Evaluation of thyroid dysfunction among type 2 diabetic patients - Raghuwanshi, Pranav Kumar; Rajput, Devendra Pratap Singh; Ratre, Bhupendra Kumar; Jain, Roopesh; Patel, Narmada; Jain, Sudeep (Asian Journal of Medical Sciences, 2014)
Background: Diabetes mellitus is a very common endocrinal disorders and incidence of thyroid dysfunction also rising in India and world over. Thyroid hormones directly control insulin secretion and insulin clearance. Diabetes also may affect the thyroid function to variable extent first at the level of hypothalamic control of TSH release and second at peripheral tissue by converting T4 to T3. Aims and Objectives: The present study was carried out aiming to evaluate thyroid dysfunction among type 2 diabetes mellitus patients. Material and Methods: Study included total 80 subjects. Thyroid dysfunction was evaluated by investigating the subjects for Total tri-iodo-thyronine (T3), Total thyroxine (T4) and thyroid stimulating hormone (TSH). Plasma glucose was estimated by- GOD-POD method and Thyroid profile was estimated by- CLIA (chemiluminescence immunoassay) system. Statistical analysis was performed using software statistical package for social sciences (SPSS) version 20, unpaired T test, Pearson’s correlation. Results: In type 2 diabetic patients the prevalence of hypothyroidism and subclinical hypothyroidism was found to be 4(10.00%) and 6(15.00%) respectively, while the prevalence of subclinical hyperthyroidism and hyperthyroidism was found to be 0(0.0%) and 1(2.5%) respectively. In non diabetic healthy subjects the prevalence of hypothyroidism and subclinical hypothyroidism was found to be 1(2.5%) and 3(7.5%) respectively while the prevalence of subclinical hyperthyroidism and hyperthyroidism was found to be 0(0.0%) and 0(0.0%) respectively. Conclusion: The prevalence of thyroid dysfunction was found to be higher in type 2 diabetes mellitus subjects as compared to non-diabetic subjects. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10814 Asian Journal of Medical Sciences Vol.6(3) 2015 33-37